Influence of job characteristics on engagement: does support at work act as moderator?. Issue 1 (14th March 2017) - Rai, Alka; Ghosh, Piyali; Chauhan, Ragini; Mehta, Navin Kumar
Abstract : Purpose: Indian banking industry is one the biggest players in the country's service sector, with public sector banks (PSBs) occupying the major share. The purpose of this paper is to develop a model linking job characteristics (JC) and work engagement, moderated by perceived organizational and supervisor support as contextual variables. Design/methodology/approach: Data on 214 employees from 15 PSBs were used to examine this model. Analysis of data has established the moderating role of support at work in the relationship between JC and work engagement. Findings: Findings suggest that employees who have a positive perception of organizational and supervisor support are more likely to respond positively to JC and therefore would have a higher propensity to engage with their jobs. In addition to enriched jobs, the wider organizational climate characterized by support from supervisors and organization as a whole is critical to establish a positive environment, which would lead to greater work engagement. Originality/value: The moderating role of support at workplace on JC and work engagement has been researched very rarely in literature. This study, hence, aims at investigating whether interaction between JC and perceived organizational and supervisor support influences work engagement of employees working in Indian PSBs.